Metode Service Quality untuk Mengetahui Tingkat Kepuasan Pelanggan di Apotek Wong Kito - Malina Nst, Wiwik; Nita Syahputri (Universitas Methodist Indonesia, 2025)
This study aims to determine the level of customer satisfaction at Wong Kito Pharmacy using the Service Quality (Servqual) method. The Servqual method is employed to measure the gap between customer expectations and perceptions of the services provided by the pharmacy based on five main dimensions: tangibles, reliability, responsiveness, assurance, and empathy. This research applies a quantitative approach using a survey method. Data were collected through questionnaires distributed to customers of Wong Kito Pharmacy. The results show that several service dimensions have negative gap values, indicating that the services received by customers are still below their expectations. The dimension with the largest gap is responsiveness, while the best-performing dimension is assurance. Overall, the level of customer satisfaction with the services at Wong Kito Pharmacy is categorized as fairly satisfied; however, improvements are still needed, particularly in the speed and responsiveness of employees in serving customers. These findings are expected to provide valuable input for the management of Wong Kito Pharmacy in improving service quality to meet customer expectations.